De haven van Antwerpen en haar werking - Coopman, J. (Antwerpen : Svastika, 1926)
Bibliotheek Camille Huysmans
Dedicator: Coopman, J., dedicatee: Huysmans, Camille
Nederlands
Monografie
Keywords: haven van Antwerpen; Antwerpen